CRIMINAL, JUSTICE, AND SOCIAL WELFARE POLICIES AND TOURISM AREA DEVELOPMENT : A PARADIGM STUDY OF LAW, ENVIRONMENT, AND SUSTAINABLE DEVELOPMENT - Boro, Lorraine Rangga (Ridwan Institute, 2024)
This study aims to explore and elucidate the interplay between criminal justice, social welfare, and tourism policies, and the role of law in promoting environmental preservation. The study is conducted by analyzing a number of policies and development implementation as well as response and output to the current community to create appropriate mitigation efforts in the form of criminal policies, not just in the field of jurisprudence (mere law), and three main pillars of Sustainable Development Goals (SDGs). The research is expected to provide a comprehensive understanding of the interconnectedness of these domains, particularly focusing on how legal frameworks can support and enhance environmental preservation efforts.